2011
DOI: 10.1039/c1jm10407a
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous titania photocatalysts: preparation, characterization and reaction mechanisms

Abstract: Titanium dioxide is a very important semiconductor with a high potential for applications in photocatalysis, solar cells, photochromism, sensoring, and various other areas of nanotechnology. Increasing attention has recently been focused on the simultaneous achievement of high bulk crystallinity and the formation of ordered mesoporous TiO 2 frameworks with high thermal stability. Mesoporous TiO 2 has continued to be highly active in photocatalytic applications because it is beneficial for promoting the diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
218
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 433 publications
(231 citation statements)
references
References 156 publications
2
218
0
Order By: Relevance
“…It is suggested that a low content of α-Fe 2 O 3 can increase specific surface area of heterojuctions, while a large amount of α-Fe 2 O 3 may decrease the specific surface area due to the nucleation of α-Fe 2 O 3 on the surface of BiOCl due to the limited specific surface area of BiOCl. Commonly, a high specific surface area and appropriate distribution of the pore are crucial parameters for high performance photocatalysts; these parameters facilitate electron transfer and provide a sufficient amount of interface for photocatalytic reactions, which results in higher activity (24).…”
Section: Results and Discussion Characterization Of The Photocatalystsmentioning
confidence: 99%
“…It is suggested that a low content of α-Fe 2 O 3 can increase specific surface area of heterojuctions, while a large amount of α-Fe 2 O 3 may decrease the specific surface area due to the nucleation of α-Fe 2 O 3 on the surface of BiOCl due to the limited specific surface area of BiOCl. Commonly, a high specific surface area and appropriate distribution of the pore are crucial parameters for high performance photocatalysts; these parameters facilitate electron transfer and provide a sufficient amount of interface for photocatalytic reactions, which results in higher activity (24).…”
Section: Results and Discussion Characterization Of The Photocatalystsmentioning
confidence: 99%
“…A photocatalyst with a mesoporous structure is considered to be effective in the target mentioned earlier. 28 Yang et al 7 presented a promising example to support the idea. In addition, there is almost no paper that has paid enough attention to the relationship between the mesostructure and property of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of lattice distortion 8,10,12,26,27 in the composite not only facilitates the generation of photoinduced electron-hole pairs, but also postpones their recombination. Its morphology, 8,18 specific surface area, 11,23,28 microstructure, 5,6,8,11,[26][27][28] exposure degree of the active site 13,28 and so on were reported to affect its photocatalytic property. Thus, it is interesting and valuable to integrate some of the aforementioned factors to improve the photocatalytic property of a tungsten trioxide/ titanium dioxide composite.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the techniques of the synthesis of powder and film systems based on titanium and zirconium oxides, like impregnation, chemical vapor deposition, chemical co-precipitation from solution and sol-gel technology require the use of organic precursors, considerable time and energy consumption [18][19][20]. Aside from that, the efficiency of the use of powder photocatalysts in liquid-phase processes is reduced due to the additional phase of the powder separation from suspension at the final stage.…”
Section: Introductionmentioning
confidence: 99%